UPAYA PENINGKATAN KESADARAN KESGILUT BAYI DAN BALITA MELALUI SEKOLAH IBU: BALITA SEHAT DAN BERKUALITAS DENGAN GIGI YANG SEHAT - Arya Adiningrat (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Dental and oral health problems are still not become a priority among Indonesian societies. According to the Basic Health Research data in 2018, oral and dental health problems are still quite high up to 57.6%. Oral and Dental health problems are the issues which are prone to be found in infancy that will disrupt the process of a proper growth and development. Most of Indonesian society in general and many mothers in particular do not understand correctly how to care the toddlers' teeth and to keep it healthy with a good quality. The Mother School of ‘Bunda Sholihah’ is a local community empowerment organization whose main program is to increase the capacity of mothers in optimizing child development. This activity is designed to train the mothers to have the ability to care for children's dental health and play an active role in educating the wider community. The method utilized in this community service activities were training and educational practices. The training that has been carried out consists of education in lectures, two-way discussions and role analogies, followed by assignments in the field. The number of participants in this activity was up to 45 members from the foundation of the Bunda Sholihah society in the area of Kasihan, Bantul with a total full and active participation which reached 75.5%. This activity is carried out in groups, in once a week for 4 weeks activity, so that the total implementation was 4 meetings. This program involved the service-voluntary team as the educators, members and administrators of the foundation of Bunda Sholihah School by using modules that have been prepared by the service-voluntary team. The activity partner was the Mother School of Bunda Sholihah, Bantul, Yogyakarta. The results of this program showed a significant increase in the level of mother’s knowledge in infant and toddler dental health (p <0.05) including mother’s personal motivation and consideration regarding early dental examination in toddler.